β-Defensin Strengthens Antimicrobial Peritoneal Mast Cell Response - Justyna Agier; Ewa Brzezińska-Błaszczyk; Sylwia Różalska; Magdalena Wiktorska; Sebastian Wawrocki; Paulina Żelechowska (Journal of Immunology Research)
Mast cells (MCs) are engaged in the processes of host defense, primarily via the presence of receptors responsible for the detection of pathogen-associated molecular patterns (PAMPs). Since BDs are exclusively host defense molecules, and MCs can elicit the antimicrobial response, this study is aimed at determining whether BDs might be involved in MC pathogen defense. We found that defensin BD-2 significantly augments the mRNA and protein expression of Toll-like receptors (TLRs) and retinoic acid-inducible gene-I-like receptor (RLR) essential for the detection of viral molecules, i.e., TLR3, TLR7, TLR9, and RIG-I in mature tissue rat peritoneal MCs (PMCs). We established that BD-2 might stimulate PMCs to release proinflammatory and immunoregulatory mediators and to induce a migratory response. Presented data on IgE-coated PMC upon BD-2 treatment suggest that in the case of allergies, there is an enhanced MC immune response and cell influx to the site of the ongoing infection. In conclusion, our data highlight that BD-2 might strongly influence MC features and activity, mainly by strengthening their role in the inflammatory mechanisms and controlling the activity of cells participating in antimicrobial processes.